1983
DOI: 10.1089/aid.1.1983.1.299
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Hematologic, and Histopathologic Studies in Rabbits Intrarectally Inseminated

Abstract: Rabbits subjected three times a week for 7 months to administrations of fresh homologous semen, colonic enemas, or semen (previously frozen at -70 degrees) preceded by enema were monitored by a battery of biochemical and hematologic tests and histopathologic examination. No biochemical, hematologic or histopathologic changes were observed. Negative blood cultures and serum endotoxin determinations excluded any possibility of systemic bacterial infection caused or induced by the treatments. Wide temporary varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…ALT activity was lower than the values reported in some previous studies (Lepitzki and Woolf, 1991;Tavares et al, 2004;Yazar et al, 2004;Silva et al, 2005;Elmas et al, 2006;Melillo, 2007;Jenkins, 2008). ALP activity was near to the levels in some previous studies (Hewitt et al, 1989;Lepitzki and Woolf, 1991;Melillo, 2007) and lower than the levels in some others (Yu et al, 1979;Wicher et al, 1984;Silva et al, 2005). It has been reported that serum ALP activity originates from both liver and bone and varies by age, and in young individuals serum ALP levels are higher because of rapid bone growth (Kaneko et al, 1997).…”
Section: Discussioncontrasting
confidence: 47%
“…ALT activity was lower than the values reported in some previous studies (Lepitzki and Woolf, 1991;Tavares et al, 2004;Yazar et al, 2004;Silva et al, 2005;Elmas et al, 2006;Melillo, 2007;Jenkins, 2008). ALP activity was near to the levels in some previous studies (Hewitt et al, 1989;Lepitzki and Woolf, 1991;Melillo, 2007) and lower than the levels in some others (Yu et al, 1979;Wicher et al, 1984;Silva et al, 2005). It has been reported that serum ALP activity originates from both liver and bone and varies by age, and in young individuals serum ALP levels are higher because of rapid bone growth (Kaneko et al, 1997).…”
Section: Discussioncontrasting
confidence: 47%
“…However, the alternative mechanism-a greater accessibility of bacterial endotoxin or endotoxin-like substances to the local or systemic immune system-cannot be exclud¬ ed despite negative blood cultures, failure to demonstrate serum endotoxin, and a normal appearance of the anorectal mucosa (16). In the present study a se¬ men-associated inhibitory effect on the humoral response to BSA was observed only in few animals and requires further confirmation.…”
Section: Discussionmentioning
confidence: 55%
“…Semen was collected from 20 normal NYS: (FG) male rabbits by means of an artificial vagina as reported previously (16). Fresh ejaculates were pooled and used within 15 min.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…4-6 months old, from the Wads worth Center's Griffin Laboratories were used for collection of se men twice or thrice daily, several days a week, for 9 months. Ejacu late was obtained by means of an artificial vagina and teaser female rabbits [9]. Sera for antibody assay were drawn from 20 of these rabbits before and at various times during semen collection.…”
Section: Methodsmentioning
confidence: 99%